Cytology, function and dynamics of stem and progenitor cells in decapod crustaceans - Vogt, Günter (Biological reviews, 2022)
Stem cells play key roles in development, tissue homeostasis, regeneration, ageing and diseases. Comprehensive reviews on stem cells are available for the determinately growing mammals and insects and some lower invertebrates like hydra but are rare for larger, indeterminately growing invertebrates that can live for many decades. This paper reviews the cytology, function and dynamics of stem and progenitor cells in the decapod crustaceans, a species-rich and ecologically and economically important animal group that includes mainly indeterminate growers but also some determinate growers. Further advantages of decapods for stem cell research are almost 1000-fold differences in body size and longevity, the regeneration of damaged appendages and the virtual absence of age-related diseases and tumours in the indeterminately growing species. The available data demonstrate that the Decapoda possess a remarkable variety of structurally and functionally different stem cells in embryos and larvae, and in the epidermis, musculature, haematopoietic tissue, heart, brain, hepatopancreas, olfactory sense organs and gonads of adults. Some of these seem to be rather continuously active over a lifetime but others are cyclically activated and silenced in periods of days, weeks and years, depending on the specific organ and function. Stem cell proliferation is triggered by signals related to development, moulting, feeding, reproduction, injury, infection, environmental enrichment and social status. Some regulatory pathways have already been identified, including the evolutionarily conserved GATA-binding and runt-domain transcription factors, the widespread neurotransmitter serotonin, the arthropod-specific hormone 20-hydroxyecdysone and the novel astakine growth factors. Knowledge of stem cells in decapods primarily refines our picture on the development, growth and maintenance of tissues and organs in this animal group. Cultured decapod stem cells have good potential for toxicity testing and virus research with practical relevance for aquaculture. Knowledge of stem cells in decapods also broadens our understanding of the evolution of stem cells and regeneration in the animal kingdom. The stem cells of long-lived, indeterminately growing decapods may hold the key to understanding how stem and progenitor cells function into old age without adverse side effects, possibly evoking new ideas for the development of anti-ageing and anti-cancer treatments in humans.